The Biology of Mosquitoes (Volume 3): Transmission of Viruses and Interactions with Bacteria - Clements, A.N (CABI, 2014)
An intended single volume to have been titled The Biology of Mosquitoes expanded into two volumes, published in 1992 and 1999, which broadly concerned mosquito physiology and mosquito behaviour, respectively. A chapter on the pathogens and parasites of mosquitoes inserted into the projected third volume expanded so greatly that it alone came to constitute this third volume, on the transmission of viruses and interactions with bacteria, plus a fourth on the transmission of unicellular and multicellular parasites, now partly written. The projected fifth volume is more distant. An important development in this volume is adoption of the revised, phylogenetic classification of mosquitoes of the tribe Aedini. Cladistic analysis of morphological data makes it possible to determine the evolutionary relationships of organisms and to produce phylogenetic classifications. This scientific advance has been adopted in recent decades by the taxonomists of most groups of living organisms, including insects, but, curiously, not by most mosquito taxonomists. Over recent years a phylogenetic classification of the culicid tribe Aedini was developed which regroups them into smaller genera with more distinct geographical distributions and, in some cases, distinctive biology - developments that have been invaluable in assembling and rationalizing a multitude of data for this review. This was most obvious in the division of the traditional genus Aedes - which has well over 900 species - into its phylogenetically distinct lineages. Because this advance in mosquito biology appears to be unknown to many, a description and justification are provided in the Introduction which immediately follows this Preface. The changes to generic names that resulted from the reclassification are detailed in Appendix 2.